Advanced gout – case study - Kądziela, Małgorzata; Klonowska, Iga (European Journal of Clinical and Experimental Medicine, 2014)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Gout is a disease caused by a deposit of monosodium urate crystals in the tissue. Joints are frequently affected, which is usually manifested by attacks of severe pain, swelling of the affected joint. The deposit of monosodium urate crystals is caused by the increased level of uric acid in the blood (hyperuricemia) above 6.5 mg / dl, which is the result of its excessive production or decreased excretion from the body. Gout occurs in 1-2% of the population, mostly middle-aged and elderly men (7% of men over 65 suffer from this condition). Women are diagnosed with gout less frequently, and the disease develops almost exclusively after menopause[1]. The incidence of gout clearly increases together with population ageing, lifestyle changes and eating habits. Excessive production of uric acid may be also caused by taking diuretics (especially thiazides) and acetylsalicylic acid in lower doses as well as high consumption of meat, seafood and alcohol (especially beer). This paper presents a case of 55-year-old man suffering from gout in chronic (advanced) stage with significant damage to the locomotor system. The first symptoms suggested a diagnosis of early stages of rheumatoid arthritis. Only after some time gout symptoms became more evident. The patient was treated with uric acid production blockers since the onset of the disease occurred. Even though he also used a low-purine diet and rehabilitation, a high level of uric acid in blood stream still maintained and joint destruction progressed. The only chance to improve the function of the locomotor system considering this patient it seems to be a surgical procedure removing the tophi around the joints or a new generation of drugs such as: febuxostat.